Polarized compartmentalization of organelles in growth cones from developing optic tectum (The Rockefeller University Press, 1985)
We have used computer-assisted reconstructions of continuous serial sections to study the cytoplasmic organization of growth cones in vivo. Optic tecta from 6.25-6.5-d-old chicken embryos were quick-frozen and then freeze-substituted in acetone-osmium tetroxide or, for comparison, prepared by conventional fixation. Images of eight freeze-substituted and two conventionally fixed growth cones were reconstructed from aligned serial micrographs. After freeze-substitution, numerous lumenless membrane-bound sacs arrayed in multilamellar stacks appear to replace the abundant smooth endoplasmic reticulum found after chemical fixation. Microtubule fascicles progressively diverge from their typical fascicular organization in the initial segment of the growth cone and are absent in the varicosity and the more distal segment. Mitochondria, in contrast, are concentrated in the proximal segment of the varicosity; multilamellar stacks and endosome-like vacuoles are in the distal segment; and coated pits and vesicles are concentrated near the terminal filopodium, which is the most distal and organelle-poor domain of the growth cone. These observations suggest that dilation and fusion of the lumenless, membrane-bound sacs that occurs during chemical fixation give rise to the network of smooth endoplasmic reticulum. The three-dimensional reconstructions show that the cytoplasmic components of growth cones, including the membrane-bound sacs and multilamellar stacks revealed by freeze substitution, are polarized along the axis of these growth cones, which suggests that they have a role in recycling of membrane during elongation of the growth cone.